Synthetic, Structural, Thermal and Biological Studies of Zr(IV), Th(IV) and VO(IV) Chelates with bis-Bidentate Schiff Bases - M. Patil, Raju; R. Chaurasiya, Shivkumar (Asian Journal of Chemistry, 2010)
Zr(IV), Th(IV) and VO(IV) chelates with N,N'-bis-[2-hydroxynapthalidine]- 4,4'-diaminodiphenylmethane [H2-NaIDADPM](L1) and N,N'-bis-[2-hydroxynapthalidine]benzidine [H2-NaIBz](L2), respectively have been synthesized and characterized by elemental analysis, magnetic susceptibility, spectral techniques like UV-Visible, IR, NMR, ESR and thermal studies. The molar conductivity data indicates that the chelates are non-electrolytes. Analytical data supports 1:1 (M:L) stoichiometry. The electronic spectra along with the magnetic data suggest octahedral geometry for VO(lV) chelates and revealed diamagnetic nature of the thorium and zirconium chelates. IR data shows the ligands function as bis-bidentate ligand coordinating through ON-NO donor system. The antimicrobial activities of the ligands and their metal chelates have been studied by screening the compounds against some selected microorganisms and the results have been compared.